2016
DOI: 10.7547/15-004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Becaplermin Gel on Diabetic Foot Ulcer Healing

Abstract: Background: A comparison of the cost-effectiveness of becaplermin plus good wound care (BGWC) versus good wound care (GWC) alone in treating patients with diabetic foot ulcers (DFUs) may enable physicians and health-care decision makers in the United States to make better-informed choices about treating DFUs, which currently contribute to a substantial portion of the economic burden of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
1
18
0
3
Order By: Relevance
“…21 Despite these statistics, there have only been a limited number of economic analyses comparing alternative treatments with standard care for the management of DFUs in the US. [22][23][24][25][26][27][28] The findings from these analyses pertaining to standard care are concordant with the findings of the present study, which showed that use of adjunctive SIS instead of standard care alone has the potential to improve outcomes for patients and reduce the burden imposed by DFUs to third-party payers. Nevertheless, generalising the findings from this study to other health-care systems would be challenging, since resource use and the manner in which resources are reimbursed by Medicare in the US would undoubtedly be different from that in other countries.…”
Section: Discussionsupporting
confidence: 88%
“…21 Despite these statistics, there have only been a limited number of economic analyses comparing alternative treatments with standard care for the management of DFUs in the US. [22][23][24][25][26][27][28] The findings from these analyses pertaining to standard care are concordant with the findings of the present study, which showed that use of adjunctive SIS instead of standard care alone has the potential to improve outcomes for patients and reduce the burden imposed by DFUs to third-party payers. Nevertheless, generalising the findings from this study to other health-care systems would be challenging, since resource use and the manner in which resources are reimbursed by Medicare in the US would undoubtedly be different from that in other countries.…”
Section: Discussionsupporting
confidence: 88%
“…Nineteen studies were included in the final analysis. All papers [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] were full economic evaluations considering and comparing the costs and benefits of interventions against comparators.…”
Section: Plos Onementioning
confidence: 99%
“…Patients across all age groups 18 years and over were captured. Four cohorts were derived from clinical trials [44,50,57,58] and some studies focused on moderate to severe, [48,[55][56][57] or non-healing [44] DFUs only. DFU infection was a part of the clinical presentation or model pathway in all studies.…”
Section: Economic Evaluation Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been considerable advancements in the understanding of the biochemical pathways and mechanisms underlying skin regenerative therapies, leading to explorations into the use of cells and cell-derived cytokines and exosomes, as well as hydrogels (recently reviewed in [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]) ( Table 1 ). While decellularized dermal scaffolds are routinely employed [ 20 ], only a PDGF (Platelet Derived Growth Factor)-related product has received regulatory approval among the cytokines, while no cell therapy has widespread approval in the U.S. [ 21 , 22 ]. Thus, rather than reliance on sophisticated biologics, the current standard of care for skin wounds continues to employ preventive measures and surgical interventions involving debridement, autologous skin grafts, or the introduction of decellularized allogeneic or xenogeneic biological scaffolds.…”
Section: Introduction—skin Wounds As a Medical Challengementioning
confidence: 99%